2017
DOI: 10.1136/vr.104053
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐rater agreement in radiographic canine hip dysplasia evaluation

Abstract: The objective was to determine the agreement between scrutineers assessing canine hip dysplasia (CHD) within and between the Fédération Cynologique Internationale (FCI) and the Swiss (CH) grading schemes, and between first-opinion and second-opinion scrutineers using the CH scheme. 62 scrutineers, participating in a quality assessment programme, were asked to evaluate 12 sets of hip radiographs. All radiographs had been previously evaluated by a first-opinion and 7 by both a first-opinion and second-opinion sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…Based on our review of the literature, there are no repeatability studies available for comparisons of radiographic grading of elbow dysplasia in dogs. However, according to repeatability studies of another prevalent radiographic screening method—the Fédération Cynologique Internationale (FCI) hip dysplasia scoring system—proportions of agreement have ranged from 46.3% to 71.3%, and Kappa values from .46 to .76 14–16 . Thus, the interobserver consistency of INC grade found in our study appears to be higher than what has been reported for hip dysplasia.…”
Section: Discussioncontrasting
confidence: 67%
“…Based on our review of the literature, there are no repeatability studies available for comparisons of radiographic grading of elbow dysplasia in dogs. However, according to repeatability studies of another prevalent radiographic screening method—the Fédération Cynologique Internationale (FCI) hip dysplasia scoring system—proportions of agreement have ranged from 46.3% to 71.3%, and Kappa values from .46 to .76 14–16 . Thus, the interobserver consistency of INC grade found in our study appears to be higher than what has been reported for hip dysplasia.…”
Section: Discussioncontrasting
confidence: 67%
“…The DI is calculated using the distance between the acetabular and the femoral head centre divided by the radius of the femoral head. The FCI grading system has relatively poor interobserver agreement 13,14 although the reproducibility of the NA seems to be sufficient. 15 For the PennHIP method, a study was published and showed high within-and between-examiner repeatability.…”
Section: Introductionmentioning
confidence: 99%
“…The FCI allows official reading of hips through visual image evaluation by a veterinarian scrutineer selected by local breed clubs; consequently, the quality of the scoring is subjective and may vary greatly [ 8 ]. This may justify the poor inter-observer agreement reported by some studies [ 9 , 11 ]. On the other hand, with respect to the FCI grading, NA measurement shows sufficient reproducibility, even among less-experienced examiners [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 96%
“…As a result of relying solely on a qualitative methodology to evaluate both hip congruency and osteoarthritis, there is some subjectivity, and the accuracy of the scoring varies with the training and expertise of the examiner [ 9 ]. Studies have shown low intra-observer and inter-observer agreement when it comes to the assessment of hip morphological characteristics and hip scoring according to FCI standards [ 10 , 11 , 12 ]. Thus, there is a demand for a more effective and reliable means to evaluate HD based on hip congruency and other joint conformation parameters.…”
Section: Introductionmentioning
confidence: 99%